(untitled) (American & British Studies Annual, 2011)
Despite the fact that George MacDonald wrote more than 90 different books during his life, only a small number seem to have caught the attention of scholars. The only comprehensive study is the psychological interpretation by Robert Lee Wolff The Golden Key. The major shortcoming of Wolff’s analysis is its subjectivity, in that Wolff includes only a psychological interpretation of the eleven fairy tales. The present paper provides an analysis of characters in George MacDonald’s stories. MacDonald has been referred to as an “unconventional traditionalist”. He proves how well he is acquainted with the genre conventions of the traditional fairy tale, then comments on and toys with these conventions, which include parody, irony, and puns. In order to discuss the characters in George MacDonald’s fairy tales, we will divide them into two large groups: human and supernatural characters.